Fish consumption by traditional subsistence villagers of the Rio Madeira (Amazon): Impact on hair mercury - Oliveira, Ronaldo C.; Dórea, José G.; Bernardi, José V. E.; Bastos, Wanderley R.; Almeida, Ronaldo; Manzatto, Ângelo G. (Annals of human biology, 2010)
Abstract Background: Subsistence ribeirinhos of the Amazon Basin depend on fish for their principal source of protein, but fish availability changes with seasonal high and low waters. Aim: To assess taxa and quantity of fish consumed and estimate attendant exposure to methyl-Hg in a traditional subsistence high fish-eating community of the Amazon Basin. Subjects and methods: 120 villagers in 18 households were followed for 6 months (August to February) for weighed portions of fish consumed. Results: Mean daily per capita fish consumption was high (406 g/day) with fish meals ranging from 4 to 14 times/week and an integrated yearly consumption of 148.2 kg/person. Median total-Hg concentrations in fish ranged from 0.011 to 0.409 ppm; six of the more consumed fish species comprised more than 50% of the fish consumed. The villagers mean hair-Hg concentration was high (17.4 ± 11.5 μg/g), with both inter- and intra-household variation despite similar high fish consumption; only 7% showed hair-Hg concentrations < 5 μg/g, but 75% had hair-Hg levels above 10 μg/g. Maternal hair-Hg was significantly correlated with respective children's hair-Hg (Spearman r = 0.5390; p < 0.0001). The high daily fish intake of these villagers is predominantly of species with much lower Hg concentrations. Conclusion: In Amazonian lifestyle of ribeirinho communities traditional fish consumption is high and depends on available species; fish is also the principal via of meHg exposure and attendant hair-Hg concentrations.